Proverbs 28:20–22 and avarice among youths in the Enugu metropolis, Nigeria - Chisom S. Ugwuewo; Stanley N. Nweze (In die Skriflig, 2025)
The strong desire to amass wealth and make money in every possible way is not a recent phenomenon; however, it is particularly intensified in contemporary times, especially among young people in the Enugu metropolis. Recent studies indicate that the average young person in Nigeria in general, and in the Enugu metropolis specifically, will seize any opportunity to acquire money, regardless of whether the means are licit or illicit, humane or inhumane. This study aims to address this social ill in the Enugu State by analysing Proverbs 28:20–22 for its relevance to the youth in the Enugu. The sapiential corpus in Proverbs 28:20–22 warns against such exorbitant desire, highlighting the eventual consequences of avarice. The text asserts that those guilty of avarice cannot expect lasting prosperity; rather, misery is inevitable. This study employs a rhetorical analytical method. Data were collected and analysed qualitatively. It is evident that the avarice of young people in Nigeria and in the Enugu metropolis has contributed to kidnapping, cybercrime (including yahoo and yahoo plus fraud), commercial male and female prostitution, moral laxity, human ritual sacrifice, rape, wasteful expenditure, sudden death, and related vices. These issues have rendered society vulnerable to crisis, thereby creating an urgent need for intervention. Despite numerous studies on crime in society, few have focused on theft and related crimes among youth in the Enugu metropolis. Moreover, none of the existing literature addresses cybercrime among young people in Igboland in general, and the Enugu metropolis specifically, from the perspective of Proverbs 28:20–22. The researchers posit that proper knowledge and application of this passage could provide a viable solution to the consequences of avarice in the Enugu metropolis.